Association between self-reported oral health and life satisfaction among China's migrant elderly following children: The mediating effect of social support - Wang, Jieru; Pang, Mingli; Kong, Fanlei (Frontiers in Public Health, 2023)
Purpose: Focusing on the life satisfaction of the migrant elderly following children (MEFC) is of great theoretical and practical significance. We aimed to examine the effect of self-reported oral health on life satisfaction among the MEFC in Weifang, China, and to further explore the mediating role of social support on the relationship between self-reported oral health and life satisfaction. Methods: We conducted a cross-sectional survey for 613 participants using multi-stage random sampling in Weifang, China, in August 2021. Social Support Rating Scale to social support for MEFC. We used the Chinese version of the Geriatric Oral Health Assessment Index (GOHAI) to evaluate self-reported oral health. We assessed life satisfaction for the MEFC via the Satisfaction with Life Scale. The data were scrutinized through descriptive analysis, a chi-square test, a t-test, Pearson correlation analysis, and structural equation modeling (SEM). Results: The mean GOHAI, social support, and life satisfaction scores were 54.95±7.618, 38.88±8.682, and 27.87±5.584, respectively. SEM analysis indicated that the self-reported oral health of the MEFC exerted a positive effect on life satisfaction and social support, and social support had a positive and direct effect on life satisfaction. Social support partially mediated the association between self-reported oral health and life satisfaction (95% confidence interval: 0.023–0.107, P<0.001), with its mediating effect accounting for 27.86% of the total effect. Conclusion: The mean score of life satisfaction was 27.87±5.584 among the MEFC in Weifang, China, suggesting relatively high life satisfaction. Our findings underscore an empirical association between self-reported oral health and life satisfaction and imply that social support mediates this relationship.